ANALYSIS OF MUSCULOSKELETAL DISCOMFORT IN SELF-PROPELLED FOREST MACHINE OPERATORS - Lima, Roldão Carlos Andrade; Rocha, Qüinny Soares; Pandolfo, Paloma Trevisan; Miyajima, Ricardo Hideaki; Simões, Danilo (Floresta, 2025)
Recent innovations in wood harvesting, with a view to improving forest operations techniques, have allowed operators to be pioneers in the use of new technologies. On the other hand, there is the emergence of a new class of occupational diseases related to musculoskeletal disorders that may be associated with this advance. In this way, it was evaluated whether operators of self-propelled forest machines of the full tree system are susceptible to musculoskeletal discomfort at levels of intensity that are harmful to occupational health. The Nordic Musculoskeletal Questionnaire was applied to identify the body parts with the highest reports of discomfort and the degree of intensity of these discomforts indicated by feller buncher, grapple skidder and grapple saw operators in Eucalyptus planted forests. The body regions with reports of discomfort were the lower back and shoulder regions, with a moderate degree of intensity. The grapple skidder is the self-propelled forestry machine with the highest number of operators experiencing discomfort during work.